(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Construction industries are known to be hazardous due to complex tasks, change of worklocation, climatic conditions and temporary organizational management. The consequences of thesehazards may involve occupational diseases, injuries and fatality. Injuries and accident rates are high in aconstruction site when compared with other manufacturing industries. Safety is one of the key factors inconstruction sites to mitigate the severity of the risk. Assessing the performance of the site concerningsafety is an important part of the management system as it provides information on the safety of theworker as well as the task. Hence the aim of this research is to investigate the site safety performanceand propose a methodology for enhancement. This is done in basically four parts viz., quantification ofrisk involved in each task, accounting for unsafe supervision, selection of right worker for the right taskand usage of PPEs. Safety performance cannot be measured only with the accidentsinjuries in the sitebut the factors which influence the unplanned events have to be highlighted while determining theperformance rate. The factors include the taskconditions of the site. Risk involved in each task isquantified using Hazard Identification and Risk Assessment (HIRA) technique. The hazards in the sitesare identified through direct observation and previous safety reports and the risk values are determinedusing likelihood and severity ratings of each hazard.